PERAN PRODUK SEMBAKO ASAL MALAYSIA TERHADAP PEMENUHAN KEBUTUHAN RUMAH TANGGA MASYARAKAT PERBATASAN INDONESIA DI KABUPATEN SAMBAS - Yuniarti, Desi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The title of this research is the impact of basic food products from Malaysia on meeting the household needs of Indonesian border communites in Sambas district. Aruk is one of the border areas in Indonesia-Malaysia. With the construction of the National Border Crossing Post (PLBN) as an official channel to support cross. border trade between countries. The aim of this research is. the author would like to identify and describe the processes of the role of products from Malaysia in meeting the needs of Indonesian Community Households.